Inflammatory Breast Cancer: An Update - Ueno, Naoto T.; Cristofanilli, Massimo; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
Inflammatory breast cancer is the most deadly subtype of breast cancer because it can spread to other organs despite of multidisciplinary approach. However, the molecular characteristic of this aggressive disease is yet to be established. This book is the one of the few textbooks that summarizes the latest information dated to inflammatory breast cancer. The uniqueness of this book is that it has summarized the latest molecular and mechanistic findings, which may lead to novel diagnostic tool or therapeutic approach to fight this deadly disease.
Keywords: Medicine; Oncology; Biomedicine; Biomedicine general; Cancer Research; Oncology